Additive effects of mitral regurgitation on left ventricular strain in essential hypertensive patients as evaluated by cardiac magnetic resonance feature tracking - Tang, Si-Shi; Shi, Rui; Zhang, Yi; Li, Yuan; Li, Xue-Ming; Yan, Wei-Feng; Jiang, Li; Yang, Zhi-Gang (Frontiers in Cardiovascular Medicine, 2022)
Objectives Hypertension is one of the leading risk factors for cardiovascular disease. Mitral regurgitation (MR) is a frequently occurring heart valve disease in hypertensive cases. This study aims to assess the effect of MR on left ventricle (LV) strain impairment among essential hypertensive cases and determine factors that independently impacted LV global peak strain. Materials and methods We enrolled 184 essential hypertensive patients, among which 53 were patients with MR [HTN(MR+) group] and 131 were without MR [HTN (MR-)group]. A further 61 age-and gender-matched controls were also included in this study. All participants had received cardiac magnetic resonance examination. The HTN (MR+) group was classified into three subsets based on regurgitation fraction, comprising mild MR (n = 22), moderate MR (n = 19), and severe MR (n = 12). We compared the LV function and strain parameters across different groups. Moreover, we performed multivariate linear regression to determine the independent factors affecting LV global radial peak strain (GRS), circumferential peak strain (GCS), and global longitudinal peak strain (GLS). Results HTN (MR-) cases exhibited markedly impaired GLS and peak diastolic strain rate (PDSR), but preserved LV ejection fraction (LVEF) compared to the controls. However, the HTN (MR+) patients showed decreased LVEF and further deteriorated GRS, GCS, GLS, PDSR, and peak systolic strain rate (PSSR) compared to the HTN(MR-) group and controls. With the aggravation of the degrees of regurgitation, LV strain parameters reduced progressively in HTN(MR+) patients. Even the mild MR group showed impaired GRS, GCS, GLS, PDSR and PSSR compared to the HTN(MR-) group. Multiple regression analyses indicated that the degree of regurgitation was independently associated with GRS (β=−0.348), GCS (β=−0.339), and GLS (β=−0.344) in HTN(MR+) patients. Conclusion GLS was significantly impaired in HTN (MR-) patients. MR may further exacerbate the deterioration of LV strain among essential hypertensive cases. Besides, the degree of regurgitation was independently correlated with GRS, GCS, and GLS in HTN(MR+) patients.